2021
DOI: 10.7759/cureus.15032
|View full text |Cite
|
Sign up to set email alerts
|

The Neurophysiology of Caffeine as a Central Nervous System Stimulant and the Resultant Effects on Cognitive Function

Abstract: Caffeine is one of the world's most consumed drugs. According to the Washington Post (2015), two billion cups of coffee are consumed per day worldwide. Caffeine is classified as a central nervous system (CNS) stimulant and an organic molecule called methylxanthine. Caffeine has three notable mechanisms of action on the CNS that produce a psychostimulant effect. These effects are responsible for the effect that caffeine has on cognitive function. The effects of caffeine consumption on cognitive function have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…At the same time, caffeine affects the cognitive function as it has three important mechanisms of action that have a psychostimulant effect on the central nervous system ( 10 ). Caffeine indirectly affects the release of neurotransmitters as it can act as a competitive antagonist against the depressant effects of adenosine ( 11 ). When this system is affected, mood, memory, alertness, cognitive function, and balance system are also affected.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, caffeine affects the cognitive function as it has three important mechanisms of action that have a psychostimulant effect on the central nervous system ( 10 ). Caffeine indirectly affects the release of neurotransmitters as it can act as a competitive antagonist against the depressant effects of adenosine ( 11 ). When this system is affected, mood, memory, alertness, cognitive function, and balance system are also affected.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that supplementation with caffeine ( 38 ), the combination of caffeine and taurine ( 34 ), caffeine and L-theanine ( 39 ), tyrosine ( 40 ), and mango leaves extract ( 41 ) can improve the RT in different cognitive and computerized tests. In this study, we showed that a dietary multi-ingredient nootropic improves the processing speed of information in young healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…A particularity of caffeine compared to other nutritive principles is the negligible pre-systemic metabolism which occurs in the liver, resulting in high absorption rates [ 6 ]. In addition, being a hydrophobic molecule, caffeine easily crosses the blood–brain barrier (BBB) and reaches the central nervous system (CNS), where it is also found in high concentrations [ 7 ]. At the CNS level, the substance exerts its neuro-stimulating action, increasing the degree of alertness and reducing fatigue, leading to better performance in psychomotor tasks requiring fast reactions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%